1999
DOI: 10.1046/j.1471-4159.1999.0730254.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Mouse Sialic Acid on Gangliosides of a Human Glioma Grown as a Xenograft in SCID Mice

Abstract: Ganglioside sialic acid content was examined in the U87-MG human glioma grown as cultured cells and as a xenograft in severe combined imunodeficiency (SCID) mice. The cultured cells and the xenograft possessed N-glycolylneuraminic acid (NeuGc)-containing gangliosides, despite the inability of human cells to synthesize NeuGc. Human cells express only N-acetylneuraminic acid (NeuAc)-containing gangliosides, whereas mouse cells express both NeuAc-and NeuGc-containing gangliosides. Small amounts of NeuGc gangliosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 54 publications
1
28
0
Order By: Relevance
“…In this study, we evaluated the effects of DR on the orthotopic growth of two mouse syngeneic brain tumors, CT-2A (malignant astrocytoma) and ependymoblastoma (EPEN), and the human U87-MG glioma xenograft. These mouse and human tumors differ in cell origin, angiogenicity, host environment, and biochemical composition, as described previously (27)(28)(29)(30)(31). Whereas tumor growth was rapid with unrestricted feeding, a moderate 40% DR significantly enhanced apoptosis while reducing growth and vascularity in all brain tumor models.…”
Section: Introductionmentioning
confidence: 58%
See 1 more Smart Citation
“…In this study, we evaluated the effects of DR on the orthotopic growth of two mouse syngeneic brain tumors, CT-2A (malignant astrocytoma) and ependymoblastoma (EPEN), and the human U87-MG glioma xenograft. These mouse and human tumors differ in cell origin, angiogenicity, host environment, and biochemical composition, as described previously (27)(28)(29)(30)(31). Whereas tumor growth was rapid with unrestricted feeding, a moderate 40% DR significantly enhanced apoptosis while reducing growth and vascularity in all brain tumor models.…”
Section: Introductionmentioning
confidence: 58%
“…The morphological, biochemical, and growth characteristics of these mouse brain tumors have been described previously (27)(28)(29)(35)(36)(37). The human cell line U87-MG was originally derived from a malignant glioma (glioblastoma) and grown as a nonsyngeneic xenograft in the SCID mice (31). All of the tumors were maintained as serial intracerebral transplants in the Boston College Animal Care Facility.…”
Section: Introductionmentioning
confidence: 99%
“…The receptor for SeV is sialic acid bound to gangliosides, which is present on most cell types including the human glia and glioma cells (22,23). It may be altered by infiltration of the host cells in the xenograft models (24) and this probably affects the infection efficiency of hIL2-SeV/DMDF and resultant efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…We previously showed that most NeuGc-containing gangliosides present in mouse brain tumours and in human glioma xenografts are derived from tumour-associated host cells (macrophages) and from the mouse serum (Ecsedy et al, , 1999Seyfried et al, 1998). Since most NeuGc-containing gangliosides in mouse serum are synthesized in the liver (Cotterchio and Seyfried, 1994), we suggest that the marked reduction of NeuG-containing gangliosides in the i.c.-grown brain tumours results in large part from the NB-DNJ-induced inhibition of ganglioside biosynthesis in the liver.…”
Section: Discussionmentioning
confidence: 99%